The Combined Thermal and Mechanical Effect of an Interstitial Gas on Thermal Rectification Between Periodically Grooved Surfaces - Chumak, Kostyantyn; Martynyak, Rostyslav (Frontiers in Mechanical Engineering, 2019)
This paper presents a study on the combined thermal and mechanical effect of interstitial gas on thermal rectification between a periodically grooved surface and a flat one. To evaluate the interstitial medium influence, the analytico-numerical solution to the corresponding thermoelastic contact problem is constructed taking into account the effect of thermal strains on gap deformation. The results are provided for the Stainless Steel AISI 304 – Aluminum Alloy A380 pair in the presence of air or krypton in the interface gaps. The effects of the gas thermal conductivity and pressure, the imposed pressure and heat flux, and the maximum groove height on the effective thermal contact resistance and the level of thermal rectification are analyzed. It is revealed that taking into account the mechanical effect of the gap filler leads to lower values of thermal rectification level. Also, the change of the gap filler thermal conductivity has more pronounced effect that the change of its pressure.